2017
DOI: 10.5194/nhess-2017-413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GLOFs in the WOS: bibliometrics, geographies and global trends of research of glacial lake outburst floods (Web of Science, 1979–2016)

Abstract: Abstract.Research of glacial lake outburst floods (GLOFs) -specific low frequency, high magnitude floods originating in glacial lakes, including jokulhlaups -is well justified in the context of glacier ice loss and glacial lake evolution in glacierised areas all over the world. Increasing GLOF research activities, which are documented by the increasing number of published research items, have been observed in the past few decades; however, a comprehensive insight into the GLOF research community, its global bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Globally, the size and abundance of glacier lakes has doubled between 1990 and 2017 (Shugar et al., 2020). Most of the growth in glacier lake area has been tied to moraine‐dammed lakes (Buckel et al., 2018; Emmer et al., 2020; Rick et al., 2022; Wilson et al., 2018; Zheng, Allen, et al., 2021), motivating numerous GLOF hazard and risk appraisals (Emmer, 2018). However, our assessment is consistent with other regional assessments that noted a lack of any long‐term, continuous increase in the frequency of moraine‐dam failures (Emmer et al., 2020; Veh et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, the size and abundance of glacier lakes has doubled between 1990 and 2017 (Shugar et al., 2020). Most of the growth in glacier lake area has been tied to moraine‐dammed lakes (Buckel et al., 2018; Emmer et al., 2020; Rick et al., 2022; Wilson et al., 2018; Zheng, Allen, et al., 2021), motivating numerous GLOF hazard and risk appraisals (Emmer, 2018). However, our assessment is consistent with other regional assessments that noted a lack of any long‐term, continuous increase in the frequency of moraine‐dam failures (Emmer et al., 2020; Veh et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To measure annual research interest in GLOFs, we refrained from a bibliometric analysis, as research on GLOFs before 2000 was low: Emmer (2018) found only 170 GLOF research articles listed on the Web of Science between 1979 and 2000. The low publication activity on GLOFs contrasts with the long research tradition on glaciers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hindu Kush Himalayas have been subjected to many glacial lake studies (Emmer, 2018; Fujita et al, 2013; Ives et al, 2010; King et al, 2017, 2018; Maharjan et al, 2018; Schwanghart et al, 2016; Veh et al, 2019), including the ones carried out for specific countries such as Nepal (Mool et al, 2011; Rounce et al, 2017; Somos‐Valenzuela et al, 2015), Bhutan (Komori, 2008; Ukita et al, 2011), and Tibet (Chen et al, 2007; Cui et al, 2011; Wang et al, 2011). Studies carried out for the Indian Himalayas include the work of ICIMOD (Ives et al, 2010) that created a comprehensive glacial lake inventory of Hindu Kush Himalayas and included three Indian states.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics takes quantitative and qualitative analysis, adopts mathematical and statistical methods, and aimed at the distribution of citation counts and the publication of journals and articles as time goes on. [ 3 ] Bibliometrics has been widely applied to various fields including medicine, ecology, geology, etc., [ 4 6 ] and has also been employed in the ophthalmic field. For example, in the study of dry eye, Boudry et al [ 7 ] used the VOSviewer software (Leiden, The Netherlands) to execute a bibliometric analysis of dry eye disease on Web of science database, ultimately got the research trends of dry eye, and Schargus et al [ 8 ] have selected studies published in the Institute of Scientific Information database (1900–2016) on dry eye research, offers scholars with a exhaustive analysis on the most cited dry eye literatures, Ramin et al [ 9 ] ran HistCite software (Eugene Garfield, Institute for Scientific Information) to analyze 20 years of glaucoma research, Caglar et al [ 10 ] resorted to the correlation analysis in routine statistics to find out the rule of diabetic retinopathy paper from 1980 to 2014.…”
Section: Introductionmentioning
confidence: 99%